2010
DOI: 10.1203/00006450-201011001-00738
|View full text |Cite
|
Sign up to set email alerts
|

738 Physical Complaints of Haitian Children in Refugee Camps Two Weeks After the 2010 Earthquake

Abstract: Aims: To look at the association between level of social deprivation and incidence of penetrating trauma in children in London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…Previous reports have confirmed that maternal treatment with allopurinol crosses the ovine (Masaoka et al 2005; Derks et al 2010), porcine (van Dijk et al 2008), and human (Boda et al 1999; Torrance et al 2009) placenta to increase fetal plasma concentrations of allopurinol and oxypurinol. In sheep, a dose of 20 mg kg −1 i.v.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Previous reports have confirmed that maternal treatment with allopurinol crosses the ovine (Masaoka et al 2005; Derks et al 2010), porcine (van Dijk et al 2008), and human (Boda et al 1999; Torrance et al 2009) placenta to increase fetal plasma concentrations of allopurinol and oxypurinol. In sheep, a dose of 20 mg kg −1 i.v.…”
Section: Discussionmentioning
confidence: 85%
“…Despite intense basic science research and clinical trials investigating the potential neuroprotective effects of the xanthine oxidase inhibitor allopurinol on the fetal brain during and following acute fetal hypoxia (Boda et al 1984; Van Bel et al 1998; Benders et al 2006; Derks et al 2006, 2010; van Dijk et al 2008; Kaandorp et al 2010, 2011a,b), no animal model exists that offers the possibility of maternal administration of allopurinol and long-term follow up of the treated offspring. Here, we show that allopurinol administered orally to the pregnant rat during late pregnancy leads to therapeutic rises in circulating allopurinol and oxypurinol in the mother and fetus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations